(untitled) (Mustansiria Dental Journal, 2024)
Aim of the study: The objective of this study was to evaluate the shear bond strength of acrylic denture teeth to different PMMA/MgO % (2%, 4%, and 6%) reinforcing nanofillers Materials and method: 40 specimens of heat cure acrylic resin (PMMA) were prepared and divided into four groups 10 specimens for each group as follows; Control Group (Group1) without MgO nano filler particles; Group (2) with 2% by weight of MgO; Group (3) with 4% by weight of MgO and Group (4) with 6% by weight of MgO. Wax pattern sample which used for acrylic cylindrical shape fabrication were (25 mm in length and 5mm in diameter, the base of the cylinder which is 5mm in thickness and 8mm in length). Shear bond strength of all specimens was evaluated. Results: Showed in the PMMA+MgO 4% showed the maximum mean value of upper bound of shear bond strength which was equaled to (14.859) while the control group PMMA recorded the minimum value of lower bound of shear bond strength (8.190). Conclusion: There was no significant difference between control group PMMA and (PMMA+MgO 2%, PMMA+MgO 6%), but there was a significant difference between PMMA+Mgo4% compared with control group PMMA.